2010
DOI: 10.1002/asia.201000093
|View full text |Cite
|
Sign up to set email alerts
|

Benzophosphole Oxide and Sulfide for Thermally Stable Cathode Buffer Layers in Organic Thin‐Film Photovoltaic Devices

Abstract: Don′t touch! Benzophosphole derivatives, which have a high glass transition temperature and resistance to crystallization, are shown to be useful as cathode buffer materials for OPV devices. The benzophosphole‐based devices showed an improvement in power conversion efficiency by annealing, which can be ascribed to the decrease in the contact resistance between the buffer layer and the adjoining layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 29 publications
0
34
1
Order By: Relevance
“…In contrast the d-BCP/Al interface was not as uniform and had a roughness of 20.8 ± 0.3 Å. Under thermal stress the NR profile began to change at 90 °C, which is above the reported bulk glass transition temperatures of CBP [25][26][27] and BCP, [28][29][30] but below that of TCTA. [31,32] Modeling showed that the change was consistent with the d-BCP layer beginning to diffuse into the emissive guest:host layer ( Figure 2).…”
Section: Doi: 101002/adma201104029mentioning
confidence: 84%
“…In contrast the d-BCP/Al interface was not as uniform and had a roughness of 20.8 ± 0.3 Å. Under thermal stress the NR profile began to change at 90 °C, which is above the reported bulk glass transition temperatures of CBP [25][26][27] and BCP, [28][29][30] but below that of TCTA. [31,32] Modeling showed that the change was consistent with the d-BCP layer beginning to diffuse into the emissive guest:host layer ( Figure 2).…”
Section: Doi: 101002/adma201104029mentioning
confidence: 84%
“…This level is slightly higher than those of the phenyl‐substituted benzodiphospholes (ca. −3.05 eV) that are used as a cathode buffer layer in OPVs . The LUMO levels of 2 c , 4 a , and 4 c are also estimated to be −3.13, −3.09, and −3.17 eV, respectively, which are comparable to or even lower than those of the phenyl‐substituted benzodiphospholes.…”
Section: Resultsmentioning
confidence: 97%
“…These benzodiphospholes have been synthesized through an intramolecular cyclization reaction of 1,4‐bis(phenylethynyl)benzene derivatives. It is notable that the benzodiphospholes were applied to OPVs as a cathode buffer layer . Additionally, Liu and co‐workers reported the synthesis of aromatic‐fused benzodiphospholes through a radical phosphanylation reaction .…”
Section: Introductionmentioning
confidence: 99%
“…These materials of diastereomeric phospholes show good high‐temperature morphological stability and high glass‐transition temperatures ( T g =148 °C). Improvements of the device performance from 2.9 to 4.6 % upon post‐annealing is attributed to the reduced contact resistance of the n ‐layer and the Al cathode facilitated by phosphole P=S−metal interactions of the buffer layer …”
Section: Cyclic Structures Containing Phosphorus and Other Heteroelemmentioning
confidence: 99%